42‐2: Self‐Scalable UV Blocking Artificial Iris Operated by Radially Controlled Crosslinking Density with Fast Switching Dynamics - Cho, Young‐Min; Nauman, Asad; Lee, Jae‐Won; Shin, Jung‐Yeop; Seo, Jin‐Hyeok; Kim, Hak‐Rin (SID International Symposium Digest of technical papers, 2024)
In the anatomy of human eye, the role of iris is crucial since it controls the light level entering the eye and enhances the visibility. Here, we propose a soft contact lens type artificial iris actuated by eternal UV (ultra‐violet) light source, self‐regulating its effective aperture size by varying the crosslinking density of bio‐compatible polymer matrix doped with photochromic dye. For its self‐regulating characteristic, we cured HEMA‐based polymer matrix gradually from center to edge. Since the polymer matrix is polymerized by heat, we utilized NIR (near infra‐red) lamp and gradient grayscale patterned photomask for its gradual characteristic. Thereby, the crosslinking density of central position is higher compared to that of peripheral, causing slow switching dynamics. The gradient difference in switching dynamics leads to artificial iris gaining self‐regulation dynamics of effective aperture. The manufactured artificial iris shows advantage in blocking UV light, self‐regulating, and fast switching dynamics. The switching dynamics of artificial iris under bright and dim light adaptation are less than 50 seconds and 120 seconds, showing similar property with human iris.